TARdYS: design and prototype of an exoplanet hunter for TAO using a R6 echelle grating - Rukdee, Surangkhana; Tala, Marcelo (Experimental astronomy, 2019)
One limitation in characterizing exoplanet candidates is the availability of infrared, high-resolution spectrographs. An important factor in the scarcity of high precision IR spectrographs is the high cost of these instruments. We present a new optical design, which leads to a cost-effective solution. Our instrument is a high-resolution (R = 60,000) infrared spectrograph with a R6 Echelle grating and an image slicer. We compare the best possible performance of quasi-Littrow and White Pupil setups, and prefer the latter because it achieves higher image quality. The instrument is proposed for the University of Tokyo Atacama Observatory (TAO) 6.5 m telescope in Chile. The Tao Aiuc high Resolution (d) Y band Spectrograph (TARdYS) covers 0.843-1.117 μ m. To reduce the cost, we squeeze 42 spectral orders onto a 1K detector with a semi-cryogenic solution. We obtain excellent resolution even when taking realistic manufacturing and alignment tolerances as well as thermal variations into account. In this paper, we present early results from the prototype of this spectrograph at ambient temperature.